Preparation of Cs–La–Sb/SiO2 catalyst and its performance for the synthesis of methyl acrylate by aldol condensation. Issue 41 (7th May 2015) - Wang, Yanan; Lang, Xuewei; Zhao, Guoqing; Chen, Huanhui; Fan, Yiwei; Yu, Linqing; Ma, Xiuxiu; Zhu, Zhirong
<x xml:space="preserve">Abstract</x> The bifunctional Cs–La–Sb/SiO2 catalyst prepared by ultrasonic impregnation showed good catalytic performance and stability for the synthesis of methyl acrylate by aldol condensation of formaldehyde and methyl acetate.